Pengaruh Desain Arsitektur Kontemporer terhadap Penguatan Identitas Merek (Studi Kasus: Pusat Oleh-Oleh Malang Strudel) - Salsabila Novitania; Heru Subiyantoro (Universitas Medan Area, 2026)
This study explores the role of contemporary architecture in strengthening brand identity at the Malang Strudel souvenir center. Contemporary architecture is viewed not only as a physical enclosure but also as a visual communication tool capable of creating a strong first impression and a memorable spatial experience for visitors. The research employs a quantitative approach using a survey method through a five-point Likert scale questionnaire distributed to 20 active visitors of Malang Strudel. Descriptive analysis results indicate that most respondents responded positively to architectural elements such as geometric forms, modern materials, natural lighting, and efficient yet comfortable spatial arrangements. These elements have been shown to enhance visual appeal, create pleasant spatial experiences, and strengthen brand identity on an emotional level. Therefore, strategically designed contemporary architecture significantly contributes to building a strong and sustainable brand image within commercial souvenir spaces.